Clinical-epidemiologic characteristic of insults in Tomsk - T. N. Nikolayeva; V. M. Alifirova; M. A. Titova (Бюллетень сибирской медицины, 2006)
Epidemiologic indices of brain insult using register method based upon recommendation of National Association on insults fight are studied. Morbidity, mortality and lethality from insults is shown taking as an example an open population of Kirovski region of Tomsk. Main risk factors and their influence on the disease outcomes are revealed.